Interplay among patient empowerment and clinical and person-centered outcomes in type 2 diabetes. The BENCH-D study. Issue 9 (September 2015) - Rossi, Maria Chiara; Lucisano, Giuseppe; Funnell, Martha; Pintaudi, Basilio; Bulotta, Angela; Gentile, Sandro; Scardapane, Marco; Skovlund, Soren Eik; Vespasiani, Giacomo; Nicolucci, Antonio; the BENCH-D Study Group, 1
Highlights Measurement of empowerment and patient-centered outcomes can be standardized. Empowerment is efficiently measured by DES-SF questionnaire. Empowerment is associated with clinical and psychosocial outcomes and self-care. DES-SF mean scores varies between centers due to difference in clinical practice. DES-SF can be an indicator to monitor implementation of chronic care model.